CELIAC DISEASE IN CHILDREN FROM MADEIRA ISLAND AND ITS PREVALENCE IN - Oliveira, Joana Raquel Henriques (2014)
ABSTRACT - Context - It is well recognized that celiac disease is an immune-mediated systemic disorder highly prevalent among relatives of celiac patients. Objectives - The aim of this study is to determine the prevalence of celiac disease in a group of first egree relatives of celiac children, and to access the frequency of human leukocyte antigen HLA-DQ2 and DQ8 in celiac disease patients and their affected relatives. Methods - A survey was conducted of 39 children with celiac disease with follow-up in the Pediatric outpatient’s clinic of Dr. Nélio Mendonça Hospital, in Madeira Island, Portugal. Were invited 110 first degree relatives to undergo serological screen for celiac disease with IgA antibody to human recombinant tissue transglutaminase (IgA-TGG) quantification. In all seropositive relatives, small intestinal biopsy and HLA typing was recommended. Results - HLA- typing was performed in 38 celiac patients, 28/74% DQ2 positive, 1/2% DQ8 positive and 9/24% incomplete DQ2. Positive IgA-TGG was found in five out of the 95 relatives, and CD was diagnosed in three of them. Three relatives had the presence of HLA-DQ2, two were DQ2 incomplete (DQB1*02). Conclusion - The prevalence of celiac disease among first degree celiac patients´ relatives was 3.1%, 4.5 times higher than the general Portuguese population (0,7%) witch reinforces the need of extensive diagnostic screening in this specific group. HLA-DQ2 typing may be a tool in the diagnostic approach.